The Role of Institutional Quality and Environment-Related Technologies in Environmental Degradation for BRICS - Hussain, Muzzammil; Dogan, Eyup (Elsevier Sci Ltd, 2021)
An expanding body of literature has highlighted the environment-growth nexus. However, the literature is scarce on the role of environmental technologies and institutional quality in environmental pollution. The present study aims to contribute to the existing knowledge by utilizing environment-related technologies (ERT), institutional quality (IQ), and energy consumption to investigate ecological footprints (EF) as a proxy for the environment in BRICS economies in a framework based on environmental Kuznets curve (EKC) theory. By using data from 1992 to 2016, long-and short-term relationships are estimated through cross-section augmented autoregressive distributive lag model, augmented mean group estimator, and common correlated effects mean group. The second-generation econometric tools indicate that IQ and ERT negatively affect ecological footprints, thereby implying reductions in environmental degradation. The EKC hypothesis is not validated, implying that an increase in economic activities causes an increase in pollution. Overall, BRICS economies should improve their quality of institutions and enhance investments in environmental technologies to achieve a sustainable environment in the future. Findings are robust to practical policy implications. (c) 2021 Elsevier Ltd. All rights reserved.
Hussain, Muzzammil/0000-0003-3612-7620; Hussain, Muzzammil/0000-0002-8001-4079
Keywords: Ecological Footprint; Sustainability; Environment-Related Technologies; Institutional Quality; Brics; Cs-Ardl